TWIN BLOCK (Studi Pustaka) - Evie Lamtiur; Angelica Margo (Faculty of Dentistry, Universitas Indonesia, 2015)
Young patients with class II skeletal malocclusion are often found. To avoid further discrepancy of this case, myofunctional therapy is one of the options. Functional appliance often used for such treatment. Functional appliance has been modified since activator was introduced by Andresen. With its bulky shape, activator makes difficulty for patient to speak and eat. Patient unable to wear it full time due to uncomfortness and negative facial appearance. In 1977, Clark developed twin block to overcome the weakness of previous appliances. A more simple design allows patient to be more comfortable and willing to wear it longer. Twin block is myofunctional appliance to reposition the mandible forward for skeletal class II correction with retruded mandible. This paper describes the design, clinical management effects of twin block treatment and brief case presentation using twin block appliance. Similar to the study reports found, this case revealed improvement of facial appearance, decrease overjet and overbite, improvement of molar relationship and good compliance of patient.